Knowledge and attitudes influence in implementation of household waste management program - Yemima Marnalita Hasibuan; Filson Maratur Sidjabat (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2020)
Waste is one of the big problems often faced by metropolitan cities like DKI Jakarta. The Environmental Agency of DKI Jakarta's research stated that DKI Jakarta produces 7500 tons of waste per day with 60.5% coming from residential. Therefore, the DKI Jakarta government initiated the